PENGARUH PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) (Studi Empiris Di Kabupaten/Kota Provinsi Jawa Tengah Periode Tahun 2010-2012) (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of local tax revenue and levies to revenue. The population in this study is Kabupeten / town in Central Java province in 2010-2012 period. Sampling technique in this research is to use saturated samples. The data analysis technique used is multiple linear regression. Based on the test results it can be concluded that : (a) Local Taxes significant positive effect on the original income. (b) Levies no significant positive effect on the original income.Keywords: Regional Revenue, Local Taxes, Levies